Forest Management Systems in Western Hill Nepal: A Study of Mahabharat Tract, Arghakhanchi District - Bhattarai, Lekha Nath (Journal of Nepalese Business Studies, 2007)
This article intends to examine the dimensions of existing forest management systems in the western hill of Nepal on the basis of field survey conducted in the Mahabharat tract of Arghakhanchi District. The study suggests that there is a simultaneous existence of three regimes of forest administration and management in the study area, namely state controlled system, privately owned system and the community management system. Neither the forests are protected nor any initiatives of management as such found to have launched under state controlled system. However, the privately owned forests and pastures found to have managed better and so the community managed forests tracts. Although the community forests in area and intensity seems to be still in infancy the perception of the locals was found highly enthusiastic towards it and it is found directly related to the degree of scarcity of forest products. The assessment of some of the successful community forests entails that the emerging model of community forest is getting indispensable and right option for the better management of remaining forests despite some of the impediments posed due to heterogeneity within the communities of the users, the uneven distribution of the forests across the village settlements, undefined boundaries and tedious official procedures for handing over.Journal of Nepalese Business Studies Vol.2(1) 2005 pp.56-64